KETAHANAN EKONOMI PADA MASA PANDEMI DI KAMPUNG CIKALAPA, DESA RAJAMANDALA KULON, KECAMATAN CIPATAT, KABUPATEN BANDUNG BARAT - `Agustina Rahayu, Resti; Elmania Rahayu, Elmania; Nursafitri, Gita; Dwi Utari, Destriana; Cahyati, Lisna; Sapitri, Neng; Rahmawati, Nuraida; Elsa Novita Wardani, Elsa; Aulia, Retania; Imaroh Nusaibah, Siti Ummu; Solihin, Dadin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) – Sekolah Tinggi Agama Islam (STAI) Pelita Nusa Bandung Barat, 2024)
This research was initially motivated by a community service program aimed at understanding the economic resilience of village communities during the pandemic. The study examines the development of the village, the understanding of Islamic economics in economic activities, the community's awareness, and the role of the social institution